2021
DOI: 10.3390/diagnostics11112116
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Phospholipid Metabolism Are Associated with Clinical Manifestations of Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune disease with fibrosis of the skin and/or internal organs, causing a decrease in quality of life and survival. There is no causative therapy, and the pathophysiology of the SSc remains unclear. Studies showed that lipid metabolism was relevant for autoimmune diseases, but little is known about the role of lipids in SSc. In the present study, we sought to explore the phospholipid profile of SSc by using the lipidomics approach. We also aimed to analyze lipidomics results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Our findings align with the existing literature regarding the increase of SM in the plasma of SS patients. 23 Elevated levels of SM species may be associated with atherogenesis. The hydrolysis of SM into ceramides (Cer) in atherogenic lipoproteins like LDL leads to lipoprotein aggregation and fusion, resulting in the formation of large lipoprotein aggregates resembling those found in extracellular regions of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings align with the existing literature regarding the increase of SM in the plasma of SS patients. 23 Elevated levels of SM species may be associated with atherogenesis. The hydrolysis of SM into ceramides (Cer) in atherogenic lipoproteins like LDL leads to lipoprotein aggregation and fusion, resulting in the formation of large lipoprotein aggregates resembling those found in extracellular regions of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SM­(d34:0), SM­(d40:2), and SM­(d38:1) exhibited statistical differences only between controls vs SS and SS vs SLE, indicating that the plasma profile of SM in SLE does not undergo significant alterations compared to controls (Figure ). Our findings align with the existing literature regarding the increase of SM in the plasma of SS patients . Elevated levels of SM species may be associated with atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this manner, the important role of ceramides in tissue fibrosis identified them as a promising target for the development of novel antifibrotic treatments [ 146 , 147 ]. In a case-control study of patients having a SSc diagnosis, Geroldinger-Simić and associates [ 148 ] revealed differences in the level of phospholipids (plasmalogens and SM) in the plasma of patients, compared to healthy controls ( Table 6 ). Additionally, they demonstrated that distinct clinical manifestations of SSc are associated with different alterations in the metabolism of phospholipids.…”
Section: Evidence Regarding Ceramides In Patients With Airdsmentioning
confidence: 99%